Obstetrical brachial plexus injuries: Late functional results of the Steindler procedure. (October 2014) - Gilbert, A.; Valbuena, S.; Posso, C.
We reviewed late functional results of a modified Steindler procedure in patients with obstetrical brachial plexus palsy and poor active elbow flexion. From 1982 to 2005, we reviewed final functional results and complications of 27 cases with flexion weakness of the elbow secondary to obstetrical brachial plexus injury, treated with a modified Steindler procedure. At the end of the follow-up, the mean active elbow flexion was 97° and the mean extensor lag was 10°. In the long-term follow-up, the modified Steindler procedure maintained good results in 67% of the cases in our series, and this percentage raised by 82% when the wrist extensor was present or restored before the Steindler procedure. There were poor results in 19% of the patients, but no major complications.